PREMATURE SEPARATION OF THE NORMALLY IMPLANTED PLACENTA - Z.D. SALIMOVA; M.F. DODKHOEVA; D.A. SAYDALIEVA (Avicenna Tajik State Medical University, 2023)
This paper provides a literature review on premature separation of the normally implanted placenta (PSNIP), also known as placental abruption or abruptio placentae, a severe pregnancy and childbirth complication. Acute placental abruption is an obstetric complication that causes massive internal bleeding, leading to intrauterine fetal death. The bleeding can also contribute to multiple organ failure, which is responsible for the high rates of maternal and perinatal morbidity and mortality associated with this obstetric complication. Researching various aspects of complications and preventing the occurrence of PSNIP is of great medical and social significance. PubMed and Google Scholar electronic databases were used to analyze placental abruption studies, resulting in over 3,000 sources. After considering keywords, 60 sources were selected and included in the study.